Macular Bruch membrane holes in choroidal neovascularization-related myopic macular atrophy by swept-source optical coherence tomography - Ohno-Matsui, Kyoko; Jonas, Jost B.; Spaide, Richard F. (American journal of ophthalmology, 2016)
Purpose: To determine frequency and associations of macular Bruch membrane defects in the region of macular atrophy developing after the onset of myopic choroidal neovascularization (CNV). Design: Retrospective observational case series. Methods: The study included all patients who were consecutively examined for high myopia (axial length ≥26.5mm) and CNV-related macular atrophy in the study period from June to July 2015. The patients underwent a comprehensive ophthalmologic examination including swept-source optical coherence tomography (OCT) of the macula. Main outcome measures were macular Bruch membrane defects. Results: Out of 33 eyes (28 patients) with myopic CNV-related macular atrophy, 25 eyes (76%) showed macular Bruch membrane defects, which were characterized by a lack of Bruch membrane, retinal pigment epithelium, photoreceptors, and choriocapillaris. At the edges of the macular Bruch membrane defects, the ends of the Bruch membrane were upturned, and an inward protrusion of large choroidal vessels could be detected. In the center of macular Bruch membrane defects, remnants of Bruch membrane could be crumpled. In multivariate analysis, higher prevalence of secondary macular Bruch membrane defects was significantly associated with a lower prevalence of intravitreal medical therapy (P < .001) after adjusting for larger macular atrophy area size (P < .001) and longer interval between development of the CNV and final examination (P = .42). Conclusions: Macular Bruch membrane defects belong to the hallmarks of myopic CNV-related macular atrophy. Since macular Bruch membrane defects lack photoreceptors and thus represent psychophysically an absolute scotoma, they are of profound importance for visual prognosis. As incidentally observed at study end, the prevalence of macular Bruch membrane defects may be lower if a previous myopic CNV was treated by intravitreal medical therapy.
Gesehen am 04.02.2019